Investigation of medical waste management in Gansu province, China. Issue 6 (June 2013) - Zhang, Hao-Jun; Zhang, Ying-Hua; Wang, Yan; Yang, Ya-Hong; Zhang, Jian; Wang, Yao-Ling; Wang, Jun-Ling
Medical waste is a special category of waste with potential health and environment risks. The present study aimed to explore the current status of medical waste management in western China. Seventy-four healthcare facilities were selected to assess the general status of medical waste management based upon a designed questionnaire survey. The surveyed results showed that the quantities of average medical waste generation were 0.79, 0.59 and 0.61 kg bed −1 day −1 in tertiary, secondary and primary hospitals, respectively. The incomplete segregation of domestic and medical waste generated a higher quantity of medical waste in primary hospitals (0.61 kg bed −1 day −1 ) than that in secondary hospitals. Furthermore, the effective implementation of the medical waste management system depended on national regulations, occupational safety, internal policies and administration and the qualifications and competence of the directors of the waste management department in the healthcare facilities. Therefore, sufficient training programmes and protective measures should be provided by healthcare facilities to all relevant personnel and adequate financial support and effective administrative monitoring should be performed by local authorities.